Fluoxetine Inhibits Calcium Influx in MIN6 cells - Hisab, Ahmed S. (European Scientific Journal, ESJ, 2018)
Fluoxetine, a widely used antidepressant that primarily acts as a selective serotonin reuptake inhibitor, inhibits various membrane receptors and Ca 2+ influx by unknown mechanism. In addition, it has been shown that Ca2+ is control mitochondrial metabolism and respiration. Here, effect of fluoxetine on the voltage gated Calcium channels in MIN6 cells was examined. Using Ca 2+ imaging is to assess intracellular calcium. Fluoxetine 30 ÂµM inhibited ca 2+ levels. These results indicated a tighter binding of fluoxetine to the Calcium than to the resting state of other channels, suggesting a more potent inhibition of Ca 2+ channels at physiological resting membrane potential. Altogether, these data demonstrate that clinically relevant concentrations of fluoxetine exert a voltage-dependent block of channels that may contribute to this antidepressantâ€™s pharmacological effects.